The Relationship Between Mahram Adopted Children is Reviewed from Islamic Law and Government Regulation No.54 Of 2007 Concerning Adoption of Children in Indonesia - Lailatul Arifah At Tambuni; Salwa Shofiatul Khulqi; Shofi Hatul Fitria; Ade Jamarudin (Zona Law And Public Administration Indonesia, 2023)
For every married couple, the desire to have children is a human nature and instinct and basically the children are entrusted to the husband and wife on the commission of Allah SWT. Every parent has high expectations for the child he cares for, seeing him as a gift that can improve his status and dignity as an adult. Facts prove that many families are beautiful and harmonious, but many rifts are caused by having to separate because they do not have children. In social life, the family is the smallest foundation of society. The writing of this article is carried out using normative juridical and empirical juridical methods where normative juridical is carried out by basing on applicable laws and regulations while empirical juridical is based on the implementation of laws and regulations that apply to society. Government Regulation No. 54 of 2007 concerning Child Adoption also states that, the relationship between children is not broken with the existence of child adoption institutions as stipulated in Article 4 of the Child Adoption Regulations that, the adoption of children does not break the blood relationship between the adopted child and his biological parents, Then Article 6 of the Child Adoption Regulation states that, adoptive parents must inform their adopted children about their origin and biological parents. Notification of the origin and biological parents is carried out with due regard to the readiness of the child concerned. What is meant by child readiness if psychologically and psychosocially it is estimated that the child is ready. This can usually be achieved when the child is close to the age of 18 years.